Physical Fitness Crisis in Generation Alpha A Systematic Review of Physical Activity Patterns, Screen Time, and Lifestyle Among Elementary School Students - Firna Yuniamanda; Tri Bayu Norito; Ilham; Wawan Junresti Daya; Boy Indrayana (Athena: Physical Education and Sports Journal, 2026)
Lifestyle changes among elementary school students have become increasingly evident alongside the rapid development of digital technology in daily life. Generation Alpha children are growing up in environments in which the use of smartphones, tablets, digital television, and various screen-based media is pervasive. This condition has gradually influenced children’s physical activity patterns and increased their tendency toward sedentary behavior. This study aimed to analyze the relationships among physical activity, screen time, and digital lifestyle with the physical endurance of elementary school students through a Systematic Literature Review (SLR) approach. Articles were retrieved from the Google Scholar, Scopus, ERIC, and PubMed databases using the PRISMA protocol. Following the selection process, 19 relevant articles published between 2010 and 2025 were included. The review findings indicate that high screen time is associated with low physical activity, increased sedentary behavior, declining physical fitness, disrupted sleep patterns, and diminished physical endurance in children. Furthermore, family environment, digital culture, and Physical Education (PE) instruction at school also influence the movement habits of elementary school students. These findings suggest that the physical fitness crisis among Generation Alpha is a multidimensional issue that necessitates the involvement of schools, families, and the social environment in cultivating an active lifestyle among children.